UTILIZATION OF LOCAL WISDOM UMMA KALADA IN ELEMENTARY SCHOOL IPS MATERIALS TO IMPROVE STUDENTS SOCIAL SKILLS - Heronimus Delu Pingge; Nana Supriatna; Sapriya; Abdul Azis Wahab (Jurnal Cakrawala Pendas, 2023)
Student interaction in learning activities shows a lack of cooperation, mutual taunting between students, not listening during group work, and not standing in line to collect assignments. This situation shows the low social competence of the students. The local wisdom of  umma kalada among the Loura aborigines contains the value of social skills as a guide to help students who still have low social skills. The research aimed to improve the social skills of Class IVa SDK Bali Loura students by implementing the local wisdom of  umma kalada. Qualitative research with class action research methods is used as the research design. Action research was carried out according to the spiral model of Kemmis and Taggart in three cycles, with the cycle phases consisting of planning, implementation of the action, observation and reflection. Data collection techniques through observation, learning outcomes tests and interviews. The data is analyzed to obtain individual and classic completeness scores. Results showed that social skills increased from Cycles I to III in terms of knowledge, attitudes and skills, and psychomorphically. It was concluded that the students' social skills were improved through the application of  umma kalada's local wisdom. Interaksi siswa dalam kegiatan pembelajaran menunjukkan kurangnya kerja sama, saling mengejek antar siswa, tidak saling mendengarkan saat kerja kelompok dan tidak mengantri saat mengumpulkan tugas. Situasi tersebut menunjukkan rendahnya keterampilan sosial siswa. Kearifan lokal  umma kalada pada masyarakat adat Loura mengandung nilai keterampilan sosial sebagai pedoman dalam membantu siswa yang masih rendah keterampilan sosial. Tujuan penelitian yang dilakukan adalah untuk meningkatkan keterampilan sosial siswa kelas IVa SDK Bali Loura dengan mengimplementasikan kearifan lokal  umma kalada. Desain penelitian yang digunakan adalah penelitian kualitatif dengan metode Penelitian Tindakan kelas. Penelitian tindakan dilakukan menggunakan model spiral dari Kemmis dan Taggart sebanyak tiga siklus, dengan tahapan siklus berpua perencanaan (plan), pelaksanaan tindakan (act), pengamatan (observe), dan refleksi (reflect). Teknik pengumpulan data dengan menggunakan observasi, Tes hasil belajar dan wawancara. Data dianalis untuk mendapatkan nilai ketuntasan individual dan klasikal. Hasil penelitian menunjukkan adanya peningkatan keterampilan sosial baik dari aspek pengetahuan, sikap dan keterampilan atau spikomorik dari siklus I hingga III. Dengan demikian disimpulkan adanya peningkatan keterampilan sosial siswa dengan munggunakan kearifan lokal  umma kalada.